Universal BRAF state detection by the Pyrosequencing®-based U-BRAFV600 assay - Skorokhod, Alexander (Pyrosequencing, 2015)
Malignant melanoma is a highly aggressive type of malignancy with considerable metastatic potential and frequent resistance to cytotoxic agents. BRAF mutant protein was recently recognized as therapeutic target in metastatic melanoma.We present the newly developed U-BRAFV600 approach (Patent No. 12153477.0-1404)—a universal Pyrosequencing®-based assay for mutation detection within the activation segment in exon 15 of human BRAF. We identified five different BRAF mutations in a single assay analyzing 75 different formalin-fixed paraffin-embedded samples of cutaneous melanoma metastases from 29 patients. All mutant variants were quantitatively detectable by the newly developed U-BRAFV600 assay. These results were confirmed by ultra-deep sequencing. In contrast to all other BRAF state detection methods, the U-BRAFV600 assay is capable of automated quantitative identification of at least 36 previously published BRAF mutations. Under the precaution of a minimum of 5 % mutated cells in a background of wild-type cells, the U-BRAFV600 assay design completely excludes false-negative wild-type results. The corresponding algorithm for classification of BRAF-mutated variants is provided in this chapter together with a detailed step-by-step protocol for the Pyrosequencing reaction.The single-reaction format and automation of data analysis make our approach suitable for the assessment of large clinical cohorts. Therefore, we suggest U-BRAFV600 assay as a powerful sequencing-based diagnostic tool to automatically identify BRAF status.